The Role of the Indonesian Attorney General's Office in Capital Market Law Enforcement (a Case Study of PT Asuransi Jiwasraya) - Iddo Andua Ramadhan; Sri Wahyu Handayani; Abdul Aziz Nasihuddin (Journal of Creative Power and Ambition (JCPA), 2026)
The capital market serves as a strategic instrument in national economic development, acting as a vehicle for fund mobilization and investment. However, the complexity of transactions within the capital market sector also creates opportunities for financial crimes that result in state financial losses and diminished investor confidence. One of the most significant cases involves corruption at PT. Asuransi Jiwasraya (Persero), characterized by the misuse of investments through capital market instruments. This study aims to analyze the authority and role of the Indonesian Attorney General's Office (Kejaksaan RI) in capital market law enforcement and to examine its implementation in handling the PT. Asuransi Jiwasraya case. The study employs a normative legal research method, utilizing statutory, conceptual, and case-based approaches. Legal materials were gathered through a literature review comprising primary, secondary, and tertiary sources and analyzed qualitatively using a descriptive-prescriptive method and deductive reasoning. The findings indicate that the Indonesian Attorney General's Office possesses strategic authority as  “dominus litis” within the criminal justice system to investigate and prosecute corruption crimes related to the capital market sector, provided the element of state financial loss is established. In the PT. Asuransi Jiwasraya case, the Office successfully proved the abuse of authority, investment manipulation, and state financial losses amounting to IDR 16.81 trillion; it also applied corporate criminal liability and utilized "follow the money" and "follow the asset" approaches in its efforts to recover state assets. The study concludes that the role of the Indonesian Attorney General's Office is not only vital for repressive law enforcement but also contributes to strengthening capital market governance, enhancing legal certainty and investor protection, and fostering the integrity of the national financial system.